Application of Risk Management Using HIRADC Method in Analytical Chemical Laboratory of University in Indonesia - Muhammad Bagus Fachrudin1, Dani Nasirul Haqi1, Putri Ayuni Alayyannur1, Noeroel Widajati1, Yenni Roh (Institute of Medico-legal Publications Pvt Ltd, 2020)
The analytical chemistry laboratory is one of laboratories at Universitas Airlangga which is often used in conducting analytical chemistry practicum activities and research for lecturers and students. In this analytical chemistry laboratory there are various chemicals and activities that are at high risk of causing danger, especially the exposure to toxic chemicals that can lead to risk of poisoning in students and laboratory staff. The purpose of this study was to apply the HIRADC method as an effort to prevent the risk of accidents and work-related illness in laboratory users. This research method is observational by observing the source of danger and the control efforts that have been made. From the results of the identification of hazards that have been made it is known that there are 10 potential hazards that can cause 10 risks. After doing the risk assessment, it is known that there are 4 low risks, 2 medium risks, 2 high risk, and 2 extreme risks. Control efforts have been made to minimize any risks. The recommendations that can be given from this study are the provision of personal protective equipment (PPE) that is in accordance with the hazards in the laboratory as well as training on how to use the PPE.